Nano céria dopada com gadolínia: condutividade elétrica e correlação com a micro e nanoestrutura - Villas-bôas, Lúcia Adriana (2013)
Solid Oxide Fuel Cells (SOFCs) are clean and efficient energy conversion devices, considered as one of the key enabling technologies for future hydrogen economy and for stationary power generation. However novel materials are needed for reducing the working temperature which limits the economic viability of fuel cells due to long-term stability problems. Ceria-based electrolytes, due to their high ionic conductivity with respect to traditional zirconia-based electrolytes, are amongst the most promising oxide-ion conductors to be used in intermediate temperature SOFCs operating at 500-700 ºC with high efficiency. The major difficulty in using ceria as electrolyte is related to Ce+4 to Ce+3 reductions, which occurs at low oxygen partial pressure and at high temperature (this is the electrolyte condition at the anode region). Another drawback in using ceria solid solutions is the poor sinterability which requires high temperatures (1400-1600 ºC) to achieve high densification (> 95%), makes the manufacturing process costly. Several approaches in research have been done to reduce the device working temperature and also the electrolyte sintering temperature. In the present work, the concomitant use of sintering aids (Co and Zn) and nanopowders was investigated. Besides this, three distinct processing routes were adopted and afterwards sintered by a two-step process. The sinterability, microstructure, electrical conductivity and electrolyte domain of Co or Zn-doped Ce0.8Gd0.2O1.9 samples were evaluated against the performance of undoped powders. Cobalt or zinc additions were effective as sintering aid allowing peak sintering temperatures about 950 °C to reach densifications in excess of 93%, showing no evidence for the presence of secondary phases. The electrical properties and microstructure were dependent of processing route, additives and sintering profile. The total conductivity at 800 °C of pressed samples sintered at 1200 °C-1000 °C/10h with 0,4 mol% Zn (6.7x10-2 S/cm) and 2 mol% Co (7.4x10-2 S/cm) were similar to undoped samples (7.2x10-2 S/cm), showing that Zn and Co had a positive effect on densification without compromising the electrical conductivity and electrolyte domain.